Audit dynamics of tenure and client pressure: An auditor independence study - Anwar, Puspita Hardianti (Journal of Accounting and Digital Finance, 2024)
This study aims to analyze the effect of audit tenure and client pressure on auditor independence. It seeks to evaluate the role of auditor commitment as a moderating variable in seeing this relationship. This study uses quantitative methods with a descriptive approach; the population studied is the Public Accounting Firm located in Gowa and Makassar Regencies, Indonesia. The sample used in this study were auditors who worked at the KAP. The data analysis technique applied is moderation regression analysis with an interaction approach. This study found that professional commitment acts as a moderating variable, where professional commitment strengthens the relationship between audit tenure and auditor independence and between client pressure and auditor independence. The study implies that auditors and audit firms should balance long-term relationships with clients and independence through solid professional commitment, supported by continuous training and stricter ethical standards from regulators and policymakers.